Cognitive Evaluation in Liver Transplant Patients Under Calcineurin Inhibitor Maintenance Therapy. Issue 4 (April 2017) - Heits, Nils; Keserovic, Dalibor; Mund, Niclas; Ehmke, Nicola; Bernsmeier, Alexander; Hendricks, Alexander; Gunther, Rainer; Witt, Karsten; Becker, Thomas; Braun, Felix
Abstract : Background: Neurological disorders due to calcineurin inhibitor (CNI) treatment pose a well-known problem after liver transplantation (LTx). In this study, the impact of CNIs on cognitive functioning during maintenance therapy was analyzed. A possible improvement of cognitive functioning, compliance and health-related quality of life (HRQoL) after conversion to a once-daily tacrolimus formulation was prospectively assessed. Methods: In a cross-section analysis cognitive functioning of living donors (LD), waiting list patients and LTx patients was tested using a 4 times trail making test (4-TTMT). In a further investigator-initiated trial a possible improvement of cognitive functioning, HRQoL and compliance after conversion to the once-daily tacrolimus formulation was prospectively assessed over 1 year. HRQoL was assessed using an EORTC-QLQ C30 questionnaire and patient's compliance was assessed by the Basel Assessment of Compliance with Immunosuppressive Medication Scales questionnaire. Correlated data were sex, age, time after surgery, liver disease, model of end-stage liver disease score, creatinine, CNI type, and CNI trough levels. Results: Two hundred eleven patients were included in this cross-section analysis. Twenty-seven patients agreed to participate in the investigator-initiated trial. LTx patients completed the 4-TTMT slower than living donor patients and faster than waiting list patients. Patients with twice daily cyclosporine A (CSA) formulation needed longer to finish the 4-TTMT than patients with the once-daily tacrolimus formulation. After drug conversion of a twice-daily CNI formulation to a once-daily tacrolimus formulation, CSA-treated patients needed longer to improve their cognitive functioning. HRQoL and compliance did not improve after drug conversion. Conclusions: Patients with once-daily tacrolimus formulation had a better psychomotor speed than CSA-treated patients. The conversion to once-daily tacrolimus formulation significantly improved cognitive functioning, but had no impact on HRQoL or compliance.